Enlightened planning : using systematic simplicity to clarify opportunity, risk and uncertainty for much better management decision making - Chapman, Christopher, 1972- (Routledge, 2020)
"Strategy, risk management and project management are often considered separately by those applying their principles--but at their most effective, all are dependent upon each other for success. Enlightened Planning teaches this holistic perspective and demonstrates how a synthesis of these approaches yields far greater opportunities. A strategic, calculated risk, for example, can be less inherently risky than chronic risk-aversion over time. Here, a respected specialist and teacher demonstrates how to become an "enlightened planner"; one that is aware of project, strategy and risk concerns, and their potential interplay. Following the core principle of Keep It Simple Systematically, he shows how organised, systematic thought processes can demystify the complexities of decision-making when considering a huge variety of concerns at once. Supported throughout with real-life cases from the author's considerable experiences with commercial organisations, it is also supported by a website containing even more cases, learning and teaching materials. This book is essential reading for any practitioner specialising in risk management, project management or strategy; as well as those teachers or participants in executive programmes"--